2005
DOI: 10.1530/eje.1.01870
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of serum osteoprotegerin in hypothyroid patients and its normalization with restoration of normal thyroid function

Abstract: Hypothyroidism is associated with increased morbidity from cardiovascular disease, and an increase in serum osteoprotegerin (OPG) has recently been reported to be associated with the severity of coronary heart disease and cardiovascular mortality. The present study was designed to examine whether hypothyroidism causes an increase in serum OPG, and to determine whether levothyroxine (L-T4) replacement therapy might suppress serum OPG levels in hypothyroid patients. Fifty-three hypothyroid patients with chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
0
22
0
2
Order By: Relevance
“…However, those studies included patients with autoimmune thyroid disease with unknown duration of hypothyroidism, and therefore the possibility that thyroid autoimmunity may modulate osteoprotegerin production could have been a confounding factor (19). Two of these studies included only premenopausal women (11,12) and the other one included both men and women, with no information about the postmenopausal status of these women (10). As postmenopausal status is an important regulator of serum osteoprotegerin concentrations (5, 6), those studies did not provide information about the possible interaction of the former with thyroid function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, those studies included patients with autoimmune thyroid disease with unknown duration of hypothyroidism, and therefore the possibility that thyroid autoimmunity may modulate osteoprotegerin production could have been a confounding factor (19). Two of these studies included only premenopausal women (11,12) and the other one included both men and women, with no information about the postmenopausal status of these women (10). As postmenopausal status is an important regulator of serum osteoprotegerin concentrations (5, 6), those studies did not provide information about the possible interaction of the former with thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms by which thyroid hormone deficiency increases serum osteoprotegerin have not yet been elucidated. It has been proposed that the increased cardiovascular risk associated with hypothyroidism or a reduced renal clearance of osteoprotegerin could be possible explanations (10). Furthermore, we cannot completely exclude the possibility that the elevation in serum osteoprotegerin concentrations during hypothyroidism might represent a response to the inhibition of bone metabolism that results from thyroid hormone deficiency (17,20), although this mechanism seems unlikely as osteoprotegerin usually increases in response to increased bone resorption (4), and is positively associated with osteocalcin levels (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased OPG levels in overt and subclinical hypothyroid patients and decreased OPG levels with levothyroxine therapy have been reported [16, 17]. It is clear that hypothyroidism is associated with cardiovascular disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical implications of this slow turnover in hypothyroidism have been conflicting and the influence of hypothyroidism on bone metabolism still remains poorly understood [8][9][10]. Recent studies suggested that thyroid disorders might influence serum OPG and RANKL levels [11][12][13][14]. Hypothyroid patients were reported to have higher concentrations of OPG compared to euthyroid controls [12][13][14] and that increase returned to normal once thyroid function had been normalized with levothyroxine (LT4) replacement [13,14].…”
Section: Introductionmentioning
confidence: 99%